The distribution of material footprints in Germany - Frank Pothen; Miguel Angel Tovar Rea\~nos (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
This study investigates the within-country heterogeneity of material footprints implied by households' consumption in Germany. Material footprints are defined as the amount of biomass, minerals, and fossil fuels extracted to produce the goods that households consume. Combining input-output data with households' consumption expenditures from the German sample survey of income and expenditure (EVS), we present the first comprehensive study on the distribution of material footprints among households, highlighting hot spots of unsustainable consumption patterns by household groups. Households in the quartile with the highest consumption expenditures have material footprints three times as large as those in the quartile with the lowest expenditures. Results of a microeconomic model of household's consumption behaviour estimated on the EVS data suggest that price-based instruments can reduce material footprints of luxury consumption such as leisure and private transport without imposing large burdens on low-affluence households. The material footprints caused by energy consumption do not react sensitively to price changes, suggesting that non-price policies are more effective to reduce them.
Keywords: 330; material footprint; demand system estimation; input-output analysis; sustainable consumption